An economic theory of Switzerland - Charles B. Blankart (Center for Economic Studies and ifo Institute (CESifo), 2011)
Switzerland is often viewed as a federalist curiosity and a unique form of direct democracy. But this view does not provide a proper understanding of the country. A theory of Switzerland is necessary. A consideration of the initial, exogenous geographical situation of Swiss territory provides a better understanding of the country's development. It was out of the frac-tured geography that the institutions of federalism and direct democracy as they are known today developed and established themselves. Although there was a trend to internal centralisation in the 20th century, the regional authorities have maintained their autonomy considerably better in Switzerland than in other states. An important factor is that the federal government, cantons and municipalities are each responsible for their own finances and debts. This stabilises not only the budget of regional and local authorities but also prevents interference on the part of the central government.
Keywords: H60; H70; N40; 330; fiscal federalism